PENDIDIKAN AGAMA ISLAM BERBASIS TRADISI LOKAL: STUDI MANGAJI TUJUH MALAM MASYARAKAT INDERAPURA PESISIR SELATAN - Noprijon Noprijon; Dodon Hardiman; Seprian Ilham (STKIP Subang, 2026)
Islamic Religious Education (PAI) does not only take place within the realm of formal education, but is also internalized through religious practices that are alive and thriving within the community. One form of non-formal Islamic education still practiced by the community of Inderapura, South Pesisir Regency, is the tradition of the “Mangaji Tujuh Malam” religious study session. This tradition is carried out in families struck by the tragedy of death through activities such as reciting the Qur’an, praying, and delivering religious sermons in a congregational setting for seven consecutive nights. This study aims to answer three main questions, namely: (1) what are the forms and processes of the Mangaji Tujuh Malam tradition in the Inderapura community; (2) what values of Islamic religious education are contained within this tradition; and (3) what role does the Mangaji Tujuh Malam tradition play in shaping the religious and social character of the community. This study employs a qualitative approach using a case study methodology. Data collection methods included participatory observation, in-depth interviews, and documentary analysis, involving religious leaders, community elders, religious study group leaders, and community members directly involved in the practice of the tradition. The research findings indicate that the Mangaji Tujuh Malam tradition serves not only as a religious ritual but also as a medium for Islamic religious education rooted in local traditions, internalizing the values of faith, worship, and social ethics such as compassion, solidarity, and empathy. This tradition contributes significantly to shaping a religious, moderate, and civilized community. This study recommends the strengthening and preservation of local religious traditions as part of the development of Islamic religious education based on local wisdom.